2017
DOI: 10.1002/ange.201701950
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Carbonylation of sec‐ and tert‐Alcohols

Abstract: Ag eneral palladium-catalyzed synthesis of linear esters directly from sec-and tert-alcohols is described. Compared to the classic Koch-Haaf reaction, which leads to branched products,t his new transformation gives the corresponding linear esters in high yields and selectivity.Key for this protocol is the use of an advanced palladium catalyst system with L2 (py t bpx) as the ligand. Av ariety of aliphatic and benzylic alcohols can be directly used and the catalyst efficiency for the benchmark reaction is outst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Transition metal-catalyzed carbonylation reactions represent an important toolbox to produce aldehydes and a variety of carboxylic acid derivatives. Hence, using starting materials such as olefins, [80][81][82][83] alcohols, 84 alkyl or aryl halides 85 the corresponding esters, acids, aldehydes, amides, and C 1extended alcohols 86 are straightforwardly available depending on the type of carbonylation reaction. Industrially most relevant are carbonylation's of olefins, which have been pioneered both by industrial chemists Otto Roelen (hydroformylation) 87,88 and Walter Reppe (hydroxyl-and alkoxycarbonylation) 89 .…”
Section: Improved Functional Catalysts For Carbonylation Reactionsmentioning
confidence: 99%
“…Transition metal-catalyzed carbonylation reactions represent an important toolbox to produce aldehydes and a variety of carboxylic acid derivatives. Hence, using starting materials such as olefins, [80][81][82][83] alcohols, 84 alkyl or aryl halides 85 the corresponding esters, acids, aldehydes, amides, and C 1extended alcohols 86 are straightforwardly available depending on the type of carbonylation reaction. Industrially most relevant are carbonylation's of olefins, which have been pioneered both by industrial chemists Otto Roelen (hydroformylation) 87,88 and Walter Reppe (hydroxyl-and alkoxycarbonylation) 89 .…”
Section: Improved Functional Catalysts For Carbonylation Reactionsmentioning
confidence: 99%
“…First, using cyclopenta-1,3-dien-1ylbenzene (A) under the identical conditions resulted in no formation of the desired product 3a, thus excluding the cycle diene A as an intermediate (Scheme 3a). 15 Furthermore, control experiments (Scheme 3b,c) showed that the H 2 O had little effect on the reaction, thereby highlighting the critical role of the palladium catalyst and ligands in the reaction.…”
mentioning
confidence: 99%